Experimental investigation on heat-transfer characteristics of a cylindrical cavity receiver with pressurized air in helical pipe. (January 2021) - Yanping, Zhang; Yuxuan, Chen; Chongzhe, Zou; Hu, Xiao; Falcoz, Quentin; Neveu, Pierre; Cheng, Zhang; Xiaohong, Huang
Abstract: A concentrating solar system is established for the experimental investigation on a cylindrical cavity receiver. With a built-in helical pipe, the receiver is loaded at the focus point of a parabolic dish, driven by a double-axis tracking system. The helical pipe contains pressurized air as the heat transfer fluid (HTF), heated by concentrated solar irradiation. The experimental investigation analyzed operation parameters effects on both heat losses and the thermal efficiencies, which are direct normal irradiance (DNI), the inlet temperature of HTF and the mass flow rate of HTF. This study also proposed an innovative mathematical model for experiment data processing. The results indicated the increase of DNI from 201.7 W/m 2 to 504.3 W/m 2 led to a decrease of the thermal efficiency, the increase of the inlet temperature from 150 °C to 200 °C emerged a same tendency. The increase of the mass flow rate from 0.05 kg/s to 0.11 kg/s was on the contrary, since it decreased total heat losses. Good agreements were achieved by compared numerical simulation results of previous studies to the experiment results. Subsequently, a method for thermal performance enhancement was summarized through experimental investigation results, which could be a mentionable improvement for cavity receiver research. Highlights: A built-in helical pipe receiver was experimentally investigated. The increase of DNI and inlet temperature resulted in a thermal efficiency decrease. The mass flow increasing from 0.05 kg/s to 0.11 kg/s reduced total heat losses. Modeling results agree with the experimental results.